2022
DOI: 10.3390/life12121962
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Cadmium Stress in Strawberry Plants Using Humic Acid and Silicon Applications

Abstract: (1) Background: Strawberry plants are strongly affected by heavy-metal-contaminated soils, which affects plant growth, yield and fruit quality. The aim of this work was to study the effects of a combination and individual application of silicon (Si) and humic acid (HA) on growth and development of Rubygem strawberries exposed to cadmium (Cd) in greenhouse conditions. (2) Methods: Morphological, physiological and biochemical parameters, including minerals in roots and leaves were determined. (3) Results: Cd str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 57 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Cadmium stress decreases cellular activity, physiological, and photosynthetic processes due to an imbalance in dietary requirements, metallic toxicity, osmotic, and oxidative stressors, as well as the photosynthetic process [48,49]. This study has demonstrated that the application of humic acid with selenium improves the reduction of abiotic stress (i.e., stress brought on by Cd) by keeping nutritional balance and osmotic stress in chili plants.…”
Section: Discussionmentioning
confidence: 77%
“…Cadmium stress decreases cellular activity, physiological, and photosynthetic processes due to an imbalance in dietary requirements, metallic toxicity, osmotic, and oxidative stressors, as well as the photosynthetic process [48,49]. This study has demonstrated that the application of humic acid with selenium improves the reduction of abiotic stress (i.e., stress brought on by Cd) by keeping nutritional balance and osmotic stress in chili plants.…”
Section: Discussionmentioning
confidence: 77%
“…In the study, it was determined that humic acid application increased shoot fresh weight by 10%, shoot dry weight by 6.2%, root fresh weight by 23%, root dry weight by 35.2%, shoot length by 7% and root length by 4.1% in tomato plants (Table 2). Humic acid application has been reported to increase shoot/root fresh and dry weights in tomato (Aksoy, 2019;Khan et al, 2020;Ural, 2020) and strawberry plants (Doğan, 2018). Ashraf and Raddy (2014) found that humic acid application resulted in an increase in root fresh weight in eggplant and tomato plants.…”
Section: Effects Of Humic Acid On the Growth Parametersmentioning
confidence: 99%
“…It has been recognized that utilizing biostimulants in crop production increases plant vigor, crop yield, and resistance to biotic and abiotic stressors [16,[20][21][22]. Recent studies have confirmed that these products can reduce the bioavailability of PTEs in soil and their toxic effects to plants [23][24][25]. However, the effect of biostimulants on Cd dynamics to soil and plants in contaminated soils has not been sufficiently elucidated.…”
Section: Introductionmentioning
confidence: 99%